A buffalo rumen-derived probiotic (SN-6) could effectively increase simmental growth performance by regulating fecal microbiota and metabolism - Yang, Shumin; Luo, Ji; Chen, Yingying; Wu, Rui; Liu, Huazhen; Zhou, Zutao; Akhtar, Muhammad; Xiao, Yuncai; Shi, Deshi (Frontiers in Microbiology, 2022)
Microorganisms play a key role in rumen digestion, which are often used as probiotics to promote growth in ruminants. However, it's unclear which bacteria play an important role and how they do it. To fill this gap, three bacterial strains, Bacillus pumilus (SN-3), Bacillus paralicheniformis (SN-6) and Bacillus altitudinis (SN-20) with multiple digestive enzymes secretion capability were isolated from the rumen of healthy Buffalo, SN-6 exhibited outstanding among the three strains. SN-6 secreted cellulase, laccase and amylase, and had potent inhibitory effects on Staphylococcus aureus ATCC25923 and Escherichia coli K99. In addition, SN-6 exhibited strong tolerance to artificial gastric juice, intestinal juice and high temperature. Antibiotic resistance test, virulence gene test and mouse toxicity test confirmed the safety of SN-6. SN-6 significantly increased the daily weight gain of Simmental (p<0.01), and affects the fecal microbiota structure and fecal metabolomic patterns of Simmental. There was a remarkable difference in the β diversity of fecal microflora between SN-6 and control groups (p<0.05). Further, SN-6 significantly increased the abundance of Clostridium_sensu_stricto_1, Bifidobacterium, Blautia and Cellulolyticum, decreased the relative abundance of Monoglobus, norank_f_Ruminococcacea. Moreover, SN-6 feeding significantly enriched fecal metabolites to maintain intestinal homeostasis and strengthen intestinal barrier function (i.e., 3-Indoleacrylic acid, Kynurenic acid). Finally, the microbial and metabolic function analysis indicated that SN-6 would enhance amino acid metabolism (mainly tryptophan metabolism) and lipid metabolism pathways. Overall, these results indicated that SN-6 could be used as a probiotic in ruminant, and also demonstrated the potential of Bacillus for exerting beneficial effects by regulating gut microbiota and host metabolism.